Nyonya specialties - Leong, Yee Soo (Singapore : Times Editions, 2004)
Collection of the peraranakan's rich heritage of culinary treasures from appetisers and nibbles, main courses, kuih and desserts to basic sambal, rempah and sauces
Includes index
Keywords: Cookery, Peranakan; Cookery, Chinese; Cookery, Singaporean